AB0477 Retention Rates and Clinical Outcomes in Cohorts of Patients (Biologic Naïve or Failed Prior Biologics) Treated with Intravenous Abatacept in a Real-World Setting: 6-Month Results from the Action Study. (9th June 2015) - Alten, R.; Nüßlein, H.; Galeazzi, M.; Lorenz, H.-M.; Mariette, X.; Cantagrel, A.; Chartier, M.; Poncet, C.; Rauch, C.; Le Bars, M.
Abstract : Background: The real-world ACTION study has shown abatacept (ABA) to be an effective and well-tolerated treatment for patients (pts) with RA. Previously, we reported results from ACTION in a cohort of pts enrolled between 2008 and 2010. 1 Here, 6-mth results in all pts enrolled in ACTION between 2008 and 2013 are presented. Objectives: To assess retention rates and effectiveness of IV ABA over 6 mths for all pts in the ACTION study. Methods: ACTION is a 2-yr, international, non-interventional cohort of pts with RA who initiated IV ABA in three distinct periods (line of treatment and participating countries varied by cohort owing to feasibility and access): Cohort A, May 2008 to December 2010 (biologic naïve or failed prior biologics [majority]), follow-up (FU) completed; Cohort B, September 2010 to December 2013 (biologic naïve only); and Cohort C, December 2011 to December 2013 (failed prior biologics), FU ongoing. Data from all cohorts were pooled, as pt baseline characteristics were comparable for each treatment line. ABA retention (and 95% CI) over 6 mths was estimated by Kaplan–Meier; pts were censored at the date of last available data. Safety is reported for all enrolled pts at a data cut-off of August 2014; incidence rates (IR) calculated based on pt exposure in FU. Results: 2343 pts were evaluable (1131, 550 and 662 in Cohorts A, B and C, respectively); 672 (28.7%) pts were biologic naïve and 1671 (71.3%) had failed ≥1 prior biologic agent: 726/2343 (31.0%) failed 1 biologic and 945/2343 (40.3%) ≥2 biologics. Differences between biologic-naïve pts and pts who failed prior biologics included: mean age (59.9 vs 57.0 yrs), RA duration (7.2 vs 12.1 yrs), CRP (1.66 vs 2.12 mg/dL), HAQ-DI (1.37 vs 1.50), erosive disease (58.1 vs 71.7%), use of ABA as monotherapy (16.5 vs 25.4%), and median dose of concomitant corticosteroids (5.0 vs 7.5 mg/day). Retention rate decreased with increasing number of previous biologic treatments (Figure ). Safety data represent 3371 pt-yrs of FU at data cut-off. There were 335 serious AEs in 174/2359 (7.4%) pts (56 discontinuations reported) and 22 deaths, including 2 due to opportunistic infections ( Pneumocystis jiroveci ; multi-organ failure including Candida infection). Serious infections occurred in 69 pts (IR: 2.05/100 pt-yrs) including 1 case of latent TB and 3 non-TB opportunistic infections (Cytomegalovirus, Candida and P. jiroveci ). There were 21 pts with malignancies (2 were pre-existing; IR: 0.62/100 pt-yrs), 17 with serious cardiac disorders, 12 with serious vascular disorders and 19 with serious hypersensitivity reactions. Conclusions: The findings of the real-world ACTION study are consistent with previous clinical experience and demonstrate the benefits and safety of IV abatacept in a large cohort of pts. These data confirm the trend of abatacept demonstrating improved retention and clinical outcomes when used in earlier lines of RA treatment. References: Nüßlein HG, et al. BMC Musculoskelet Disord 2014;15:14. Disclosure of Interest: R. Alten Grant/research support from: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb, H. Nüßlein Consultant for: Bristol-Myers Squibb, Abbvie, Chugai, UCB, Wyeth, Pfizer, MSD, Novartis and Roche, Speakers bureau: Bristol-Myers Squibb, Abbvie, Chugai, UCB, Wyeth, Pfizer, MSD, Novartis and Roche, M. Galeazzi: None declared, H.-M. Lorenz Consultant for: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb, X. Mariette Grant/research support from: Biogen, GSK, Pfizer, Speakers bureau: Bristol-Myers Squibb, GSK, Pfizer, sanofi, UCB, A. Cantagrel Grant/research support from: Pfizer, UCB, Roche, Chugai, Speakers bureau: Bristol-Myers Squibb, Pfizer, Chugai, Abbvie, Nordic-Pharma, Fabre, MSD, Novartis, M. Chartier Consultant for: Bristol-Myers Squibb, C. Poncet Consultant for: Bristol-Myers Squibb [full-time contractor], Employee of: DOCS, C. Rauch Employee of: Bristol-Myers Squibb, M. Le Bars Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb